2012
DOI: 10.1093/dnares/dss031
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of Microsatellites in Candidate Genes Related to Wood Properties in the Chinese White Poplar (Populus tomentosa Carr.)

Abstract: Gene-derived simple sequence repeats (genic SSRs), also known as functional markers, are often preferred over random genomic markers because they represent variation in gene coding and/or regulatory regions. We characterized 544 genic SSR loci derived from 138 candidate genes involved in wood formation, distributed throughout the genome of Populus tomentosa, a key ecological and cultivated wood production species. Of these SSRs, three-quarters were located in the promoter or intron regions, and dinucleotide (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…capitata L.), sweet potato (Ipomoea batatas L.), and white poplar (Populus tomentosa Carr.) [9,13,14,48,49], but different from coconut tree (Cocos nucifera L.), field pea (Pisum sativum L.) and fava bean (Vicia faba L.), species in which tri-nucleotides were the most abundant EST-SSR markers [14,49,50].…”
Section: Discussionmentioning
confidence: 95%
“…capitata L.), sweet potato (Ipomoea batatas L.), and white poplar (Populus tomentosa Carr.) [9,13,14,48,49], but different from coconut tree (Cocos nucifera L.), field pea (Pisum sativum L.) and fava bean (Vicia faba L.), species in which tri-nucleotides were the most abundant EST-SSR markers [14,49,50].…”
Section: Discussionmentioning
confidence: 95%
“…tomentosa individuals in Guan Xian County, Shandong Province, China (36°23′N, 115°47′E). Phylogenetic analysis of 26 species from five subgenera (sections) of the genus Populus suggested that the parental species used to produce the linkage population here potentially possess the closest relationship of any Populus species (Du et al ., ), which probably reflects the fundamental similarity in the life histories of the two species, implying a possible shared genetic basis between intra‐ and interspecific variation. Integrated mapping in these populations might open up opportunities to simultaneously decipher the common genetic nature underlying growth traits in Populus .…”
Section: Methodsmentioning
confidence: 93%
“…Of these, only a small proportion (7.2, 6.1, 6.7% for B. rapa , B. oleracea and B. napus , respectively) was involved in the previously developed publicly available Brassica SSR markers (). This finding suggests that most of these newly developed Brassica genic SSR markers could represent the new ‘functional’ markers, which should be highly useful in evolutionary studies, 29 comparative mapping, 32 candidate gene association mapping 53 and molecular breeding.…”
Section: Discussionmentioning
confidence: 99%